Protection by low-dose γ radiation on doxorubicin-induced nephropathy in rats pretreated with curcumin, green tea, garlic or l-carnitine - Rasha R. Radwan; Esmat A. Shaban; Sanaa A. Kenawy; Hesham A. Salem (Faculty of Pharmacy, Cairo University, 2012)
The protective potentials of a single exposure to 0.3 Gy of γ radiation alone or with previous treatment with certain natural products with antioxidants activity, namely curcumin (50 mg/kg, i.p.), green tea (300 mg/kg, p.o.), garlic (100 mg/kg, p.o.) or l-carnitine (40 mg/kg, i.p.) against doxorubicin (DOX)-induced nephropathy in rats were studied. Natural products were administered daily for 14 successive days followed by single i.p. injection of DOX (5 mg/kg). Rats were subjected to whole body γ radiation, 1 day before DOX administration. Serum levels of creatinine, urea, uric acid, low density lipoprotein (LDL-C), high density lipoprotein (HDL-C) cholesterols, total proteins and albumin as well as renal concentrations of reduced glutathione (GSH), thiobarbituric acid reactive substances (TBARS), nitric oxide (NO) and calcium (Ca) were determined. Irradiation provided significant protections against DOX-induced changes in all measured parameters, except renal Ca content. All the test natural products significantly improved radiation-induced protection against renal lipid peroxidation. l-Carnitine markedly augmented the protection toward changes in renal GSH, NO and Ca concentrations. Curcumin increased the protection toward changes in serum albumin and renal GSH and NO concentrations, while garlic increased the protection toward changes in serum LDL-C level. It could be concluded that low-dose γ radiation could provide prophylaxis against DOX-induced nephropathy which might be augmented by the use of certain natural antioxidants.